Pengembangan Even Pariwisata Berkelanjutan di Ubud Bali - Luh Yusni Wiarti; Dewa Ayu Made Lily Dianasari; Nyoman Dini Andiani; Fitria Earlike Anwar Sani (Pusat Kajian Bali Universitas Udayana, 2023)
This research aims to determine the priority of sustainable tourism event development strategies in Ubud-Bali with an Analytical Hierarchy Process (AHP). The concept of sustainable tourism supported by the Grand Theory Event was used as a foundation in processing in-depth interview data with Penta helix experts, resulting in nine criteria and four alternative strategies. The results showed several strategies to develop sustainable events in Ubud: improving destination image, preserving local culture, increasing global networking, and developing green events. All of these are supported by increasing the network and image of Ubud as an environmentally friendly event destination. The novelty is that the resulting strategic priorities have considered environmental aspects, local culture, and community interests in Ubud. As an implication, the result can be used as a practical guide for tourism stakeholders in developing sustainable tourism events not only in Bali but also in Indonesia and around the world.